Long-lasting insecticidal nets (LLINs) use among household members for protection against mosquito bite in Mogadishu districts - Ahmed Aweis; Abdinur A. Salad; Fathi A. Araye; Abdifatah M. Ahmed; Osman A. Wehlie; Ali Abdirahman Osman; Isaiah Gumbe Akuku (Public Library of Science (PLoS), 2023)
Understanding long-lasting insecticidal nets (LLINs) utilization is important in monitoring and quantifying the impact of past and current prevention and control efforts of malaria. A cross-sectional study was carried out on a sample of 409 households in Mogadishu, to estimate the LLIN use and assess barriers to its utilization. A standardized questionnaire was used to collect data on demographics, malaria-related knowledge, and the use of preventive measures. LLINs use was assessed using multivariable generalized estimating equations with adjustment for clustering of study participants within the same household. Out of 409 households only 155 (37.9%) owned LLINs. Out of 237 owned LLINs, 199 (84.0%) were used. Median household size being 6.0 (3.0), intra-household net accessibility was low, with one net (42.6%) frequent. Most nets were from mass distribution (55.7%) and obtained '12 months ago'. Un-partnered respondents (unadjusted odds ratio [OR] 0.34, 95% CI 0.14, 0.82; p = 0.017) compared with partnered (married) respondents, large-sized household (adjusted OR 0.83, 96% CI 0.74-0.94; p = 0.002). There was marginal evidence of a greater odds of LLIN utilization among respondents knowledgeable of the correct cause of malaria, that is, mosquito bites (AOR 3.19, 95% CI 0.77, 13.2; p = 0.11) but was not statistically significant. Among households owning nets, most of the LLINs were hung the night prior to the survey (7.9% versus 98%) and was associated with greater marginal odds of utilization (p<0.001). Ownership of LLINs is insufficient in Mogadishu districts affecting household-level access and utilization. If this is not checked, this could weaken the progress made on malaria control efforts. LLIN utilization was modest and largely driven by recently acquired nets showing a desire to utilize them despite low coverage. These imply that mass and facility-based distribution, and awareness campaigns will remain relevant, but efforts for willingness-to-pay for LLINs should be strengthened to sustain coverage and replacements of worn-out nets.